Study of the military actions' environmental impact in the east of Ukraine - Kravchenko, Olena; Vasyliuk, Olexiy; Voitsikhovska, Alla; Norenko, Kateryna (Skhid, 2015)
The dynamics of life and environment destruction in the east of Ukraine is rapidly increasing. This article analyzes the main factors of contamination and destruction of the environment as a result of the military operations in eastern Ukraine. There were held the calculations of areas destroyed by fire, analyzed the dynamics of fires in the east of Ukraine and compared with the previous years, there were analyzed the soils in the Krasnolymanskyi region and water form Siverskyi Donets River. It was found that the military operations have devastating impact on all of the environment objects without exception. For a complete evaluation of the scope of environment destruction and pollution, it is necessary to conduct environmental monitoring, to develop an action plan on restoration of the environment.